Comparative assessment of PDE 4 and 7 inhibitors as therapeutic agents in experimental autoimmune encephalomyelitis. (17th September 2013) - González‐García, C; Bravo, B; Ballester, A; Gómez‐Pérez, R; Eguiluz, C; Redondo, M; Martínez, A; Gil, C; Ballester, S
<x xml:space="preserve">Abstract</x> Background and Purpose PDE4 inhibition suppresses experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). However, side effects hinder PDE4 inhibitors clinical use. PDE7 inhibition might constitute an alternative therapeutic strategy, but few data about the anti‐inflammatory potential of PDE7 inhibitors are currently available. We have used the EAE model to perform a comparative evaluation of PDE4 and PDE7 inhibition as strategies for MS treatment. Experimental Approach Two PDE7 inhibitors, the sulfonamide derivative BRL50481 and the recently described quinazoline compound TC3.6, were assayed to modulate EAE in SJL mice, in comparison with the well‐known PDE4 inhibitor Rolipram. We evaluated clinical signs, presence of inflammatory infiltrates in CNS and anti‐inflammatory markers. We also analysed the effect of these inhibitors on the inflammatory profile of spleen cells in vitro. Key Results TC3.6 prevented EAE with efficacy similar to Rolipram, while BRL50481 had no effect on the disease. Differences between both PDE7 inhibitors are discussed. Data from Rolipram and TC3.6 showed that PDE4 and PDE7 inhibition work through both common and distinct pathways. Rolipram administration caused an increase in IL‐10 and IL‐27 expression which was not found after TC3.6 treatment. On the other hand, both inhibitors reduced IL‐17 levels, prevented infiltration in CNS and increased the expression of the T regulator cell marker Foxp3. Conclusions and Implications These results provide new information about the effects of Rolipram on EAE, underline PDE7 inhibition as a new therapeutic target for inflammatory diseases and show the value of TC3.6 to prevent EAE, with possible consequences for new therapeutic tools in MS.